Credibility of Policies Versus Credibility of Policymakers - Masson, Paul (IMF Working Papers; Working Paper, 1994)
Standard models of policy credibility, defined as the expectation that an announced policy will be carried out, emphasize the preferences of the policymaker, and the role of tough policies in signalling toughness and raising credibility. Whether a policy is carried out, however, will also reflect the state of the economy. We present a model in which a policymaker maintains a fixed parity in good times, but devalues if the unemployment rate gets too high. Our main conclusion is that if there is persistence in unemployment, observing a tough policy in a given period may lower rather than raise the credibility of a no-devaluation pledge in subsequent periods. We test this implication on data for the interest rate differential between France and Germany and find support for our hypothesis.